Productivity Loss amid Invisible Pollution - Chunchao Wang; Qianqian Lin; Yun Qiu (Global Labor Organization (GLO), 2020)
Ground-level ozone is a continuing problem worldwide, but research on the influences of ozone pollution on labour productivity in developing countries is insufficient. We investigate the effect of ozone pollution on outdoor worker productivity in the service sector using a unique panel dataset of courier productivities from a top five express company in China. Using an instrumental variable constructed from ozone pollution of upwind nearby cities, we find that a one-standard-deviation increase in daily ozone pollution decreases courier productivity by 8.91%. The same increase in ozone in the previous 30 days decreases worker productivity by 37.9%.
Keywords: J24; O13; P23; P28; Q51; Q53; 330; ozone pollution; air pollution; labour productivity; outdoor workers; contemporaneous effect; cumulative effect; express delivery industry